Clinical conditions and risk factors for inhibitor‐development in patients with haemophilia: A decade‐long prospective cohort study in Japan, J‐HIS2 (Japan Hemophilia Inhibitor Study 2). Issue 5 (11th June 2022) - Nogami, Keiji; Taki, Masashi; Matsushita, Tadashi; Kojima, Tetsuhito; Oka, Toshiaki; Ohga, Shouichi; Kawakami, Kiyoshi; Sakai, Michio; Suzuki, Takashi; Higasa, Satoshi; Horikoshi, Yasuo; Shinozawa, Keiko; et al.
Abstract: Background: Inhibitor‐development is a serious complication in patients with haemophilia (PwH). Previous studies reported that therapeutic and genetic factors could be associated with these alloantibodies. Relevant clinical features such as genetic‐background and different treatment regimens in Japan remain unclear, however. Aims: To analyse a nation‐wide Japanese registry for PwH, and to examine risk factors for inhibitor‐development. Methods and results: Newly diagnosed patients with haemophilia A (PwHA) or haemophilia B (PwHB) without inhibitors after 2007, and with treatment records traceable from 0 to 75 exposure days (ED), were enrolled in the Japan Hemophilia Inhibitor Study 2 (J‐HIS2) initiated in 2008. Of 417 patients (340 PwHA, 77 PwHB) from 46 facilities, 83 (76 PwHA, 7 PwHB) were recorded with inhibitors by July 2020. Inhibitors were observed in 31.0% of severe PwHA, 8.0% moderate and 1.6% mild and in 17.1% of severe PwHB. The majority of inhibitors (89.7% in severe PwHA and 71.4% in severe PwHB) were detected on or before 25ED (median 12ED in PwHA and 19ED in PwHB). Genotyping in these severe patients identified an association between inhibitor‐development and null variants of F8 ( P  < .01) or F9 ( P  < .05). A lower incidence of inhibitors was recorded in severe PwHA treated with prophylaxis than in those treated on‐demand ( P  < .01). A past‐history of intracranial‐haemorrhage appeared to be associated with inhibitor‐development, while FVIII‐concentrates infusion and routine vaccination on the same day was not related to inhibitor‐development. Conclusion: The J‐HIS2 study has identified significant clinical variables associated with inhibitor‐development in Japanese PwH, consistent with other global studies.